ESTRUS INDUCTION, FOLLICULAR DYNAMICS AND FERTILITY RESPONSE TO MID-CYCLE PGF2a, CIDRAND OVSYNCH PROTOCOLS IN SUBFERTILE GIRAND CROSSBRED COWS - HADIYA, K K; DHAMI, A J; NAKRANI, B B; LUNAGARIYA, P M (The Indian Journal of Animal Reproduction, 2023)
This study was carried out on 36 infertile (subestrus and repeat breeders) Girand HF x K crossbred cattle of University farm using three estrus synchronization protocols, viz., Mid-cycle PGF2n, Ovsynch and CIDR, to evaluate estrus response and conception rates clinically and through transrectal ultrasound scanning, and the findings were compared with those of 24 untreated cyclic cows. Six subestrus/repeat breeding cows each of Gir & crossbreds (6x2 = 12) having mid cycle mature CL were treated with single i/m injection of 500 ±g cloprostenol, and fix timed Al (FTAI) was performed at 72 and 96 hrs post-treatment. Similarly, six infertile cyclic Girand crossbred cows each (6x2 =12) were treated with standard CIDR protocol and equal numbers (6x2 =12) with Ovsynch protocol using FTAI on day 9 and 10. Ovarian and uterine changes were monitored using transrectal ultrasound scanning (USG) on alternate days till induced estrus/FTAI, and then at weekly interval till day 42 post-Al. Estrus induction response was 100 % with all three synchronization protocols as seen clinically and through USG. The conception rates of 12 subfertile cows, each subjected to CIDR, Ovsynch and Mid-cycle PGF2 u treatment protocols were 41.66, 41.66 and 33.33 %, respectively, at Induced estrus. The corresponding conception rates at second cycle post-treatment were 28.57, 42.85 and 25.00 %; and at third cycle 40.00, 50.00 and 33.33 %, with the overall conception rates of 3 cycles as 75.00, 83.33 and 66.66 %. In untreated cyclic control cows, the conception rates at first, second and third service and overall of 3 services were 20.83, 21.05, 26.66 and 54.16 %, respectively. The mean CL size on the day of mid-cycle PG injection was largest (14.0200.46 mm) and that of follicle smallest (4.2200.42 mm), which changed drastically (P<0.01) within 48-72 hrs and the values at induced estrus by 72 hrs post-PG treatment were almost inversed (7.7001.16 and 12.9400.74 mm). Similar were the observations for cows of CIDR and Ovsynch groups also between PG injection and induced estrus/Al. Moreover the changes noted in CL/Follicle size around day 21- 23 post-Al were in accordance with the maintenance of pregnancy or repeat cycle. One pregnant cow each in Mid-cycle PGF2_1 and Ovsynch treated groups showed early embryonic mortality between day 28 and 42 postAl. The fertility results obtained using all 3 treatment protocols were much better than that of untreated cyclic animals. Gir cattle in fact responded better with CIDR, while Crossbreds showed better results with Ovsynch, and the response with Mid-cycle PGF r treatment was relatively poor and almost same in both the classes of animals. There were positive correlations between USG data sheet and rectal palpation findings on ovarian and uterine changes following treatment/Al.